2022
DOI: 10.1063/5.0093428
|View full text |Cite
|
Sign up to set email alerts
|

The interfacial structure of super-concentration LiNO3 aqueous electrolyte studied by second harmonic generation

Abstract: Using non-resonant second harmonic generation (SHG) and heterodyne-detected SHG (HD-SHG) spectra,we studied the broadening mechanism of the electrochemical stability window (ESW) for the super-concentrated LiNO3 aqueous electrolyte. We first investigated the electric double layer structure at the air/LiNO3 interface. As the concentration of LiNO3 increased, the SHG intensity first increased and then remained unchanged, while the SHG phase changed by about 5{degree sign}. These results reveal that there was onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…The total SHG intensity, I SHG , is given by I SHG | E sam ( 2 ω ) + E ref ( 2 ω ) | 2 = | E sam ( 2 ω ) | 2 + | E ref ( 2 ω ) | 2 + 2 E sam ( 2 ω ) E ref ( 2 ω ) α cos Φ where α is the overlap parameter that represents the degree of spatial and temporal overlap, and Φ is the overall phase. Φ can be obtained by fitting the interference pattern with the following equation: I SHG = I 0 + A cos false( f x + φ fit false) where x is the stage position, and I 0 , A , f , and φ fit are fitting parameters.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total SHG intensity, I SHG , is given by I SHG | E sam ( 2 ω ) + E ref ( 2 ω ) | 2 = | E sam ( 2 ω ) | 2 + | E ref ( 2 ω ) | 2 + 2 E sam ( 2 ω ) E ref ( 2 ω ) α cos Φ where α is the overlap parameter that represents the degree of spatial and temporal overlap, and Φ is the overall phase. Φ can be obtained by fitting the interference pattern with the following equation: I SHG = I 0 + A cos false( f x + φ fit false) where x is the stage position, and I 0 , A , f , and φ fit are fitting parameters.…”
Section: Methodsmentioning
confidence: 99%
“…The total SHG intensity, I SHG , is given by where α is the overlap parameter that represents the degree of spatial and temporal overlap, and Φ is the overall phase. Φ can be obtained by fitting the interference pattern with the following equation: where x is the stage position, and I 0 , A , f , and φ fit are fitting parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the surface potential at the air/ aqueous interface can be determined using HD-SHG. [38][39][40]74 When the surface potential is opposite at the air/aqueous interface, the j sig should also be opposite. As shown in Fig.…”
Section: Orientation and Molecular Relative Number Density Of Interfa...mentioning
confidence: 99%
“…In addition, nonlinear spectroscopy heterodyne-detected second harmonic generation (HD-SHG), a special SFG process, is also a powerful tool to investigate ion specificity at the electrical double layer of the charged interface using the new w (3) model. [37][38][39] Bai et al 40 also investigated the electric double layer structure at the super-concentrated air/LiNO 3 aqueous electrolyte interface using HD-SHG. With the intrinsically interfacial sensitivity and selectivity SFG technique, Shen initially reported the molecular structure of methanol at the air/neat methanol interface, 41 and subsequently the methanol/water mixture interface was extensively studied.…”
mentioning
confidence: 99%